Heterogeneity of helper/inducer T lymphocytes. I. Lymphokine production and lymphokine responsiveness (The Rockefeller University Press, 1987)
Antigen-specific, Ia-restricted helper/inducer T lymphocytes consist of subsets that can be distinguished by lymphokine secretion. One, called Th1, secretes IL-2 and the other, termed Th2, produces BSF-1/IL-4 in response to stimulation by lectin or antigen receptor signals, and each uses the respective lymphokine as its autocrine growth factor. Cloned lines representing Th2 cells proliferate in response to both IL-2 and their autocrine lymphokine, BSF-1/IL-4, but this proliferation is dependent on the synergistic costimulator activity of the monokine, IL- 1. In contrast, Th1 clones proliferate only in response to IL-2, are unresponsive to BSF-1/IL-4, and their growth is unaffected by IL-1. These response patterns are not attributable to variations in culture conditions but apparently reflect intrinsic properties of the two T cell subsets. Moreover, the unresponsiveness of Th1 cells to BSF-1/IL-4 may be related to lower levels of expression of surface receptors for this lymphokine. These results may explain the observed heterogeneity among bulk populations of T cells in terms of lymphokine responsiveness and requirement for accessory factors (costimulators). In addition, our findings suggest that IL-2, unlike BSF-1/IL-4, is a fully competent growth factor that is potentially involved in antigen-independent expansion of bystander T cells present at sites of immune stimulation.